Maternal health and incarceration: advancing pregnancy justice through research - Camille Kramer; Denae Bradley; Rebecca J. Shlafer; Carolyn Sufrin (Health & Justice)
Abstract This paper will review the state of the science on maternal health and incarceration. We will provide a historical context on women, pregnancy, and mothers as it relates to mass incarceration, considering both structural racism and reproductive justice. We will discuss existing research that documents care, treatment, and outcomes of individuals who are incarcerated while pregnant or postpartum in the United States. We will discuss the implications of carceral exposure on birthing people and their families. By synthesizing current research and relevant policies, we will identify gaps that will then inform a research agenda for the next decade, including methods and content, to address inequities in and improve maternal and infant outcomes among pregnant and parenting people exposed to incarceration.